2003
DOI: 10.1128/iai.71.6.3034-3042.2003
|View full text |Cite
|
Sign up to set email alerts
|

Killing of Aspergillus fumigatus by Alveolar Macrophages Is Mediated by Reactive Oxidant Intermediates

Abstract: Phagocytosis and mechanisms of killing of Aspergillus fumigatus conidia by murine alveolar macrophages (AM), which are the main phagocytic cells of the innate immunity of the lung, were investigated. Engulfment of conidia by murine AM lasts 2 h. Killing of A. fumigatus conidia by AM begins after 6 h of phagocytosis. Swelling of the conidia inside the AM is a prerequisite for killing of conidia. The contributions of NADPH oxidase and inducible nitric oxide synthase to the conidicidal activity of AM were studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
354
2
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 392 publications
(382 citation statements)
references
References 37 publications
22
354
2
4
Order By: Relevance
“…Our data are consistent with those of a previous study that showed that intracellular conidial swelling is necessary to elicit production ROS by alveolar macrophages (18). In the absence of dectin-1-mediated ROS production, other, potentially less inflammatory, antimicrobial killing mechanisms may play a role in macrophage recognition and killing of inhaled, resting conidia.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our data are consistent with those of a previous study that showed that intracellular conidial swelling is necessary to elicit production ROS by alveolar macrophages (18). In the absence of dectin-1-mediated ROS production, other, potentially less inflammatory, antimicrobial killing mechanisms may play a role in macrophage recognition and killing of inhaled, resting conidia.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to inflammatory cytokine production, initial host defense to A. fumigatus involves macrophage production of ROS (18). We examined the relative abilities of resting conidia and germ tubes to induce ROS production by murine bone marrowderived macrophages.…”
Section: A Fumigatus Germ Tubes But Not Conidia Activate Proinflammentioning
confidence: 99%
“…Calcineurin inhibition delayed phagocytosis of SC in hMDMs (P , 0.01) and hAMs (P = 0.04) early postinfection, but phagocytosis of RC was not affected ( Figures 2C, E2B, and E2C). We measured reactive oxygen species (ROS) production and cathepsin B (a lysosomal cysteine protease) activation, which are critical for Af killing (22,23). ROS production was partially calcineurin dependent (P , 0.0001) but had no effect on mitochondrial ROS (Figures 2D, E2D, and E2E) or activated cathepsin B production ( Figures 2E and 2F).…”
Section: Original Articlementioning
confidence: 99%
“…In COPD patients ciliary activity impairment, immunosuppression due to alveolar macrophage and neutrophil inhibition in those treated with steroids and also receiving broad-spectrum antibiotics, play an important role in the development of IPA [54] . The most common invasive aspergillosis-associated underlying disease in ICUs is COPD, followed by SOT [53] .…”
Section: Airway Invasive Aspergillosis Is An Uncommon Invasive Diseasmentioning
confidence: 99%